Haze episodes before and during the COVID-19 shutdown in Tianjin, China: Contribution of fireworks and residential burning. (1st October 2021) - Dai, Qili; Ding, Jing; Hou, Linlu; Li, Linxuan; Cai, Ziying; Liu, Baoshuang; Song, Congbo; Bi, Xiaohui; Wu, Jianhui; Zhang, Yufen; Feng, Yinchang; Hopke, Philip K.
Abstract: Potential health benefits from improved ambient air quality during the COVID-19 shutdown have been recently reported and discussed. Despite the shutdown measures being in place, northern China still suffered severe haze episodes (HE) that are not yet fully understood, particularly how the source emissions changed. Thus, the meteorological conditions and source emissions in processing five HEs occurred in Beijing-Tianjin-Hebei area were investigated by analyzing a comprehensive real-time measurement dataset including air quality data, particle physics, optical properties, chemistry, aerosol lidar remote sensing, and meteorology. Three HEs recorded before the shutdown began were related to accumulated primary pollutants and secondary aerosol formation under unfavorable dispersion conditions. The common "business as usual" emissions from local primary sources in this highly polluted area exceeded the wintertime atmospheric diffusive capacity to disperse them. Thus, an intensive haze formed under these adverse meteorological conditions such as in the first HE, with coal combustion to be the predominant source. Positive responses to the shutdown measures were demonstrated by reduced contributions from traffic and dust during the final two HEs that overlapped the Spring and Lantern Festivals, respectively. Local meteorological dispersion during the Spring Festival was the poorest among the five HEs. Increased residential burning plus fireworks emissions contributed to the elevated PM2.5 with the potential of enhancing the HEs. Our results highlight that reductions from shutdown measures alone do not prevent the occurrence of HEs. To further reduce air pollution and thus improve public health, abatement strategies with an emphasis on residential burning are needed. Graphical abstract: Image 1 Highlights: Even with increased emissions controls, high pollution events occur in China. "Business as usual" emissions in Tianjin exceeded winter diffusive capacity. COVID shutdown reductions were offset by residential burning and fireworks. Coal combustion remains a major source of PM2.5 . Abstract : Fireworks plus residential burning contributed to the elevated PM2.5 with the potential of enhancing hazes.